2021
DOI: 10.1002/jcb.30144
|View full text |Cite
|
Sign up to set email alerts
|

The role of stem cell‐derived exosomes in the repair of cutaneous and bone tissue

Abstract: Exosomes are extracellular vesicles secreted by various cell types, which play important roles in physiological processes. In particular, stem cell-derived exosomes have been shown to play crucial functions in intercellular communication during the tissue healing process. This review summarizes the effects of exosomes derived from different stem cell sources on the repair of cutaneous and bone tissue, focusing on the different pathways that could be involved in the regeneration process. The biogenesis, isolati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…Previous works have demonstrated that the conditioned medium from SHED contains other growth factors such as angiopoietin‐2, epidermal growth factor (EGF), hepatocyte growth factor, stem cell factor, and transforming growth factor‐α, 47 but also the anti‐inflammatory cytokines TGF‐β1 and IL‐10, and proliferative cytokines IL‐6 and IL‐3, among others. Here, we also identified the cytokines CXCL8 (IL‐8), IL‐6, CSF‐1, CCL2 (MCP‐1) and growth factors such as PDGF, IGF2, IGFBPs, 2,4–7 MYDGF. Therefore, other possible signalling pathways should be explored 47,48 …”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Previous works have demonstrated that the conditioned medium from SHED contains other growth factors such as angiopoietin‐2, epidermal growth factor (EGF), hepatocyte growth factor, stem cell factor, and transforming growth factor‐α, 47 but also the anti‐inflammatory cytokines TGF‐β1 and IL‐10, and proliferative cytokines IL‐6 and IL‐3, among others. Here, we also identified the cytokines CXCL8 (IL‐8), IL‐6, CSF‐1, CCL2 (MCP‐1) and growth factors such as PDGF, IGF2, IGFBPs, 2,4–7 MYDGF. Therefore, other possible signalling pathways should be explored 47,48 …”
Section: Discussionmentioning
confidence: 96%
“…5 MSCs secretome can therefore activate different signalling pathways involved in the skin regeneration process to enhance keratinocytes, fibroblasts, and endothelial cell activities. 5 In addition, these molecules can regulate ROS and cytokine levels and contribute to the macrophage transition into an anti-inflammatory profile M2. 5 Stem cells from human exfoliated deciduous teeth (SHED) are self-renewing MSCs residing within the perivascular niche of the dental pulp.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Exosomes from different origins can be made in different forms and injected into the bone defect area to facilitate bone regeneration. Stem cells derived exosomes can promote osteogenesis through four main mechanisms: reducing apoptosis, recruiting mesenchymal stem cells and promoting their proliferation, creating an osteogenic-inducing environment to promote osteogenic differentiation of stem cells, and accelerating angiogenesis and bone vascularization ( Girón et al, 2022 ). Its applications for bone defect, bone and cartilage regeneration, osteoarthritis, osteoporosis, and osteonecrosis have been described ( Bei et al, 2021 ).…”
Section: Exosomesmentioning
confidence: 99%